A Complementary Study of the Chemical Behavior of Cesium Iodide in the Presence of Boron in the Condensed Phase (650°C and 400°C) Under Primary Circuit Conditions: Differential Thermal Analysis and Thermogravimetric Studies. (3rd July 2018) - Gouëllo, Mélany; Hokkinen, Jouni; Kärkelä, Teemu; Auvinen, Ari
Abstract: This work is a contribution to the work performed in a paper on the understanding of the chemical reactions between cesium iodide and boron oxide in condensed phase, under conditions close to the ones prevailing in the primary circuit of a nuclear power plant in case of a severe accident. The thermal degradation of samples made from cesium iodide or cesium iodide and boron oxide mixtures has been investigated using the techniques of thermogravimetric analysis and differential thermal analysis at temperatures from 20°C to 1000°C. The boron-to-cesium molar ratio in the investigated mixture was fixed at about the value of 5 (B/Cs = 5). Apart from the dehydration of boric acid, evidence is presented for the formation of a vitreous compound at 360°C to 420°C, depending on the atmosphere composition. Carrier gas composition also seemed to influence the behavior of the precursor mixture. While under air and argon, the recorded thermograms are similar. In the presence of argon/water vapor, a specific behavior and difference on reactivity is noticed, due to the adsorption of water from the carrier gas at the beginning of the process. It was also pointed out that the addition of water or oxygen delayed the glass formation process.